Bi-objective mathematical model for choosing sugarcane varieties with harvest residual biomass in energy cogeneration - Gomes, Francisco Regis Abreu (International Journal of Agricultural and Biological Engineering, 2012)
Sugarcane crop occupies an area of about 23.78 million hectares in 103 countries, and an estimated production of 1.66 billion tons, adding to this volume more than 6% to 17% concerning residual biomass resulting from harvest. The destination of this residual biomass is a major challenge to managers of mills. There are at least two alternatives which are reduction in residue production and increased output in electricity cogeneration. These two conflicting objectives are mathematically modeled as a bi-objective problem. This study developed a bi-objective mathematical model for choosing sugarcane varieties that result in maximum revenue from electricity sales and minimum gathering cost of sugarcane harvesting residual biomass. The approach used to solve the proposed model was based on the